Overview of polymeric polyplexes for dsRNA delivery in insects: complexation, stability, and design considerations - Kallavus, Triin; Willow, Jonathan; De Schutter, Kristof; Taning, Clauvis Nji Tizi; Veromann, Eve (Frontiers in Insect Science, 2026)
Polymer-based delivery systems for double-stranded RNA (dsRNA) have gained attention as a promising strategy for RNA interference (RNAi)-mediated insect pest control. Despite encouraging in vitro results, their practical application remains limited by methodological inconsistencies and species-specific challenges. Variability in experimental parameters, such as nitrogen/phosphorous (N/P) ratios, dsRNA lengths, and buffer systems, complicates reproducibility and cross-study comparisons. Moreover, in vitro stability and transfection efficiency often fail to predict in vivo RNAi outcomes, highlighting the need for more physiologically relevant models. Variation in RNAi efficiency across insect orders, such as Lepidoptera and Hemiptera, continues to challenge the generalizability of polymer-based delivery systems. To advance the field, future research should focus on species-tailored polymer design, improved predictive assays, and comprehensive environmental safety evaluations. Interdisciplinary collaboration will be essential to develop RNAi delivery platforms that are efficient, scalable, and ecologically sustainable.